1992
DOI: 10.1111/j.1752-1688.1992.tb03997.x
|View full text |Cite
|
Sign up to set email alerts
|

GIS‐ASSISTED REGRESSION ANALYSIS TO IDENTIFY SOURCES OF SELENIUM IN STREAMS1

Abstract: Using a geographic information system, a regression model has been developed to identify and to assess potential sources of selenium in the Kendrick Reclamation Project Area, Wyoming. A variety of spatially distributed factors was examined to determine which factors are most likely to affect selenium discharge in tributaries to the North Platte River. Areas of Upper Cretaceous Cody Shale and Quaternary alluvial deposits and irrigated land, length of irrigation canals, and boundaries of hydrologic subbasins of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 7 publications
0
13
0
Order By: Relevance
“…As all variables in all years showed a significant positive skewness together with kurtosis it was felt inappropriate to use annual mean values in linear regression analysis versus time. Instead annual median values were employed in regression analysis (See et al, 1992) because they are a superior measure of central tendency and resistant to the effects of outliers, typical of skewed data sets (Sokal and Rohlf, 1969). However, because of the lack of normality in the data a Mann–Whitney test (Hollander and Wolfe, 1999) was used to compare data for 1997 and 2000 rather than the conventional parametric two‐sample t test.…”
Section: Methodsmentioning
confidence: 99%
“…As all variables in all years showed a significant positive skewness together with kurtosis it was felt inappropriate to use annual mean values in linear regression analysis versus time. Instead annual median values were employed in regression analysis (See et al, 1992) because they are a superior measure of central tendency and resistant to the effects of outliers, typical of skewed data sets (Sokal and Rohlf, 1969). However, because of the lack of normality in the data a Mann–Whitney test (Hollander and Wolfe, 1999) was used to compare data for 1997 and 2000 rather than the conventional parametric two‐sample t test.…”
Section: Methodsmentioning
confidence: 99%
“…These sources are usually underlain by selenium-bearing geologic formations. Historical water-quality data show the highest selenium concentrations within the Kendrick Watershed are found primarily in irrigation waters proximal to shale-derived soils (Natrona County Conservation District, 2005;Erdman, 1989;See et al, 1992;Seiler et al, 1999). More recent water-quality data collected at nonirrigation sites in the project area also had high selenium concentrations, indicating that selenium exceedances are not limited to irrigation lands.…”
Section: Discussionmentioning
confidence: 83%
“…This analysis expands on an earlier study by See et al (1992) that applied a similar methodology of regressing watershed characteristics to predict in-stream selenium concentration. See et al (1992) found that most of the variability in median selenium loads can be explained by the area of irrigated land and the length of irrigation canals.…”
Section: Methodsmentioning
confidence: 93%
See 1 more Smart Citation
“…The HRU approach derives segments from the homogeneity of physiographic and geographic parameters. It has been widely applied with geographic information systems (GIS) and remotely sensed data to facilitate hydrological modeling (See et al, 1992;Greene and Cruise, 1995;Chen, 2007Chen, , 2008. Units with similar hydrological response can be grouped by overlying different layers of physiographic information that preserves the heterogeneity of the watershed (Flugel, 1995).…”
Section: Introductionmentioning
confidence: 99%